2016
DOI: 10.1016/j.virol.2015.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Two mutations in the vif gene of maedi-visna virus have different phenotypes, indicating more than one function of Vif

Abstract: Like most other lentiviruses, maedi-visna virus (MVV) requires Vif for replication in natural target cells and in vivo. Here, we show that Vif-deficient MVV accumulates G-A mutations in the sequence context characteristic of ovine APOBEC3, consistent with a role of MVV Vif in neutralizing APOBEC3. We studied two point mutations in the vif gene of MVV. One was a tryptophan to arginine mutation that affects the interaction with APOBEC3 and caused G-A hypermutation. The other mutation was a proline to serine muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…MVV Vif is promiscuous and degrades not only sheep A3Z3 but also the A3Z3-type proteins of other species, including human (12). Previous study has observed that mutation of W98 from the similar β sheet concave surface of MVV Vif impaired its ability to antagonize OaA3Z2Z3 (31). W98 is located near a positively charged surface (fig.…”
Section: Discussionmentioning
confidence: 99%
“…MVV Vif is promiscuous and degrades not only sheep A3Z3 but also the A3Z3-type proteins of other species, including human (12). Previous study has observed that mutation of W98 from the similar β sheet concave surface of MVV Vif impaired its ability to antagonize OaA3Z2Z3 (31). W98 is located near a positively charged surface (fig.…”
Section: Discussionmentioning
confidence: 99%
“…MVV Vif is essential for the infection of primary macrophages and for in vivo infections. 22 , 32 It degrades APOBEC3 proteins through a ubiquitin/proteasome-dependent pathway, 24 by recruiting certain cellular proteins to construct a Vif-mediated E3 ubiquitin ligase complex. These cellular proteins in sheep include the scaffold protein Cullin5 (CUL5) and the substrate adaptors Elongin B/C 25 and CYPA (also known as peptidylprolyl isomerase A), as cofactors for degrading the sheep APOBEC3.…”
Section: Srlv Infection Of the Cell – If Allowedmentioning
confidence: 99%
“…Accessory regulatory genes are located coinciding with the regions pol and env in different reading frames and contain information for the synthesis of proteins that regulate viral replication. These genes are as follows: vif , the product of which is necessary to make the virus infectious, 14 , 22 25 identified as an important factor to fight against the defense mechanisms of the cell; vpr-like , which has a function similar to that of Vpr in other lentiviruses, although initially it was considered equivalent to Tat protein in other lentiviruses, but no clear transactivation function has been associated to it; 26 and rev , which is involved in the regulation of viral expression ( Figure 2 ). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation